Influencing factors of colonoscopy screening in first-degree relatives of hospitalized colorectal cancer patients and preliminary clinical practices to improve the compliance - Zhao, Dongqin; He, Fan; Luo, Chen; Huang, Huanhuan; Zhao, Qinghua (Frontiers in Oncology, 2025)
ObjectivesThis study aimed to analyze the factors that influence colonoscopy screening in first-degree relatives (FDRs) of patients with colorectal cancer (CRC) and explore the feasibility to invite FDRs to undergo a colonoscopy to improve screening compliance.MethodsRetrospective analysis based on a prospectively collected database of which FDRs of CRC patients who visited our center between April 2021 and October 2021 and received a questionnaire surgery. The questionnaire contained three aspects: demographic and lifestyle factors, health beliefs, and disease cognition. The FDRs were invited to undergo a colonoscopy and were followed-up by telephone regarding colonoscopy compliance one year later.ResultsIn total, 303 FDRs from 256 patients with CRC were analyzed. Among them, 113 underwent colonoscopy, with a colonoscopy compliance rate of 37.3%. The results of the multivariate analysis showed that the FDRs who underwent colonoscopy were older (OR=2.32, p=0.006), had commercial insurance (OR=2.23, p=0.013), had multiple family members with CRC (OR=3.04, p=0.012), had higher cognition of CRC (OR=3.02, p=0.006), had high self-efficacy for disease screening (OR=1.14, p=0.026), and accepted colonoscopy appointment sheet to undergo colonoscopy screening (OR=4.51, p<0.001), which were influencing factors for CRC screening in FDRs.ConclusionThis study found that FDRs who were ≥40 years old, had commercial insurance, had multiple family members with CRC, had higher cognition of CRC, had high self-efficacy for disease screening, and received a colonoscopy appointment while in the hospital were more willing to undergo colonoscopy screening. Studies could further validate the feasibility of this approach in the future.